Extracellular Brain Ph with or without Hypoxia is a Marker of Profound Metabolic Derangement and Increased Mortality after Traumatic Brain Injury. Issue 3 (March 2013) - Timofeev, Ivan; Nortje, Jurgens; Al-Rawi, Pippa G; Hutchinson, Peter JA; Gupta, Arun K
Cerebral hypoxia and acidosis can follow traumatic brain injury (TBI) and are associated with increased mortality. This study aimed to evaluate a relationship between reduced pHbt and disturbances of cerebral metabolism. Prospective data from 56 patients with TBI, receiving microdialysis and Neurotrend monitoring, were analyzed. Four tissue states were defined based on pHbt and Pbt O2 : 1—low Pbt O2 /pHbt, 2—low pHbt /normal Pbt O2, 3—normal pHbt /low Pbt O2, and 4—normal pHbt /Pbt O2 ). Microdialysis values were compared between the groups. The relationship between Pbt O2 and lactate/pyruvate (LP) ratio was evaluated at different pHbt levels. Proportional contribution of each state was evaluated against mortality. As compared with the state 4, the state 3 was not different, the state 2 exhibited higher levels of lactate, LP, and glucose and the state 1—higher LP and reduced glucose ( P < 0.001). A significant negative correlation between LP and Pbt O2 (rho = −0.159, P < 0.001) was stronger at low pHbt (rho = −0.201, P < 0.001) and nonsignificant at normal pHbt ( P = 0.993). The state 2 was a significant discriminator of mortality categories ( P = 0.031). Decreased pHbt is associated with impaired metabolism. Measuring pHbt with Pbt O2 is a more robust way of detecting metabolic derangements.